A Novel Application for (222)Rn Emanation Standards: Radon-Cryptophane Host Chemistry - Laureano-Perez, L. (2012)
In collaboration with the University of Pennsylvania, a (222)Rn emanation source was used for the determination of the binding affinity of radon to a cryptophane molecular host. This source was similar to a (222)Rn emanation standard that was developed and disseminated by the National Institute of Standards and Technology (NIST). The novel experimental design involved performing the reactions at femtomole levels, developing exacting gravimetric sampling methods and making precise (222)Rn assays by liquid scintillation counting. A cryptophane-radon association constant was determined, K(A) = (49,000 ± 12,000) L· mol(−1) at 293 K, which was the first measurement of radon binding to a molecular host.